Diagnóstico para subsidiar a gestão de resíduos da construção civil na cidade de São Carlos SP - Zanutto, Talita Devides (Universidade Federal de São Carlos, 2012)
The Construction Industry is major generator of waste and use of natural resources and, therefore, while important to the economy, is causing enormous environmental impact. Regarding the generation of waste, its impact can be minimized with reduction actions at the construction site and measures of reuse and recycling. In 2002, at the Federal, passed Resolution No. 307 of the National Council on the Environment - CONAMA - which provides guidelines, criteria and procedures for the management of construction waste, in effect as of January 2, 2003. This study aims to determine the current situation of implementing the directives of this resolution in São Carlos, from the perspective of the responsibilities inherent in the companies operating in this city. For that we adopted the strategy of case study as a research method, with a structured questionnaire for use in major construction companies active in the city of São Carlos. The methodology comprised the following stages: a literature review on waste generation, structuring the questionnaire, the questionnaire was applied to a number of companies operating in the city of São Carlos and analysis of results. As a contribution stands out the diagnosis on the implementation of guidelines and procedures recommended in CONAMA Resolution No. 307 in the city of São Carlos, emphasizing the difficulties and possible ways for this to be actually applied. The results, in summary, show that employees are directly linked to the practices of construction do not know precisely, which describes the CONAMA Resolution No. 307 and construction companies, despite having practiced some activities related to the management of construction waste, not apply the concepts of law.
Keywords: Gestão de Resíduos; Resolução CONAMA 307/2002; Construção Civil; Canteiro de Obras; Reciclagem; Waste Management; Resolution CONAMA 307/2002; Construction; Construction Site; Recycling; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL